The SIOP Model: Transforming the Experiences of College Professors Part I. Lesson Planning, Building Background, and Comprenhensible Input (GIST – Education and Learning Research Journal, 2010)
This article, the first of two, presents the introduction, context, and analysis of professor experiences in an on-going research project for implementing a new educational model in a bilingual teacher’s college in Bogotá, Colombia. The model, the sheltered instruction observation protocol (SIOP) promotes eight components for a bilingual education program. These components will be analyzed to discern what educators found to be easy or challenging in their classroom teaching practice.